Hauwezi kuvuka ziwa hadi uwe na ujasiri wa kutouona urefu wa pwani: Made in Africa Evaluation as courageous conversation - Antony B. Maikuri; Vidhya Shanker; Rodney K. Hopson (African Evaluation Journal, 2022)
This article elaborates on the implications for Made in Africa Evaluation (MAE) of the results of previous research that the authors conducted on harm and the monitoring and evaluation (M&E) cycle, specifically the connection that the previous study’s participants drew between care and courage. The Kiswahili proverb that serves as the title of this article translates into English as, ‘You can never cross the ocean until you have the courage to lose sight of the shore’.
This article elaborates on the implications for Made in Africa Evaluation (MAE) of the results of previous research that the authors conducted on harm and the monitoring and evaluation (M&E) cycle, specifically the connection that the previous study’s participants drew between care and courage. The Kiswahili proverb that serves as the title of this article translates into English as, ‘You can never cross the ocean until you have the courage to lose sight of the shore’.